2017
DOI: 10.1590/s0102-865020170100000001
|View full text |Cite
|
Sign up to set email alerts
|

Erdosteine ameliorates the harmful effects of ischemia-reperfusion injury on the liver of rats

Abstract: 1 AbstractPurpose: To investigate the potential protective effects of erdosteine against the harmful effects of ischemia-reperfusion injury on the liver in an experimental rat model. Methods: Forty rats were divided into 4 groups. In the sham group, only the hepatic pedicle was mobilized. No other manipulation or treatment was performed. In the other groups, ischemia was achieved by clamping the hepatic pedicle for 60 min. After that, 90 min reperfusion was provided. In the control group, no treatment was give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Numerous experimental studies have been carried out in order to decrease the harmful effects of hepatic IRI. [6][7][8]25] However, there is still no pharmacological agent routinely used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous experimental studies have been carried out in order to decrease the harmful effects of hepatic IRI. [6][7][8]25] However, there is still no pharmacological agent routinely used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Barlas et al [25] investigated the effect of erdosteine on experimental liver IRI and found that erdosteine treatment relieved histopathological findings compared to the control group. Moreover, it was determined that this treatment improved liver function values and oxidative stress parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors such as anaerobic metabolism, oxidative stress and ROS secretion, mitochondrial damage, and cytokines play a role in regulating hepatic I/R processes 16 . Although many studies have been conducted on the application of agents with protective effects to prevent hepatic I/R injury in experimental studies, there are no studies evaluating the efficacy of ALE [17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…After detaching of liver from the ligaments and hepatic pedicule (ductus hepaticus, hepatic portal vein and proper hepatic artery) was clamped with an atraumatic microvascular clamp and hepatic ischemia in the lobus hepatis mediana and lobus hepatis sinister. After 60 minutes of ischemia, the clamp was removed and 1 ml NaCl 0.9% was administered intraperitoneally, then the abdomen was closed and we waited 1 hour for reperfusion [15]. The other hepatic lobs had taken whole portal and arterial blood supply.…”
Section: Ischemia/reperfusionmentioning
confidence: 99%